Chimeric Antigen Receptors and Regulatory T Cells: The Potential for HLA-Specific Immunosuppression in Transplantation. (March 2022) - Wright, Sabrina; Hennessy, Conor; Hester, Joanna; Issa, Fadi
Abstract: Chimeric antigen receptors (CARs) are a breakthrough in genetic engineering that have revolutionized the field of adoptive cellular therapy (ACT). Cells expressing these receptors are rerouted to a predefined target by the inclusion of an antigen-specific binding region within the synthetic CAR construct. The advantage of cells with programmed specificity has been demonstrated clinically in the field of oncology, and it is clear that such cells have greater accuracy, potency, and reduced off-target therapeutic effects compared with their unmodified counterparts. In contrast to conventional T cells (Tconvs), regulatory T cells (Tregs) play a major role in suppressing immune activation and regulating the host immune response. CAR expression within Tregs has been proposed as a therapy for autoimmune and inflammatory diseases, graft-versus-host disease (GVHD), and organ transplant rejection. In the latter, they hold immense potential as mediators of immune tolerance for recipients of allotransplants. However, current research into CAR-Treg engineering is extremely limited, and there is uncertainty regarding optimal design for therapeutic use. This review examines the rationale behind the development of CAR-Tregs, their significance for human transplantation, potential designs, safety considerations, and comparisons of CAR-Tregs in transplantation models to date.